Probing the Microstructure in Pure Al & Cu Melts: Theory Meets Experiment - Song, Lin; Tian, Xuelei; Yang, Yanmei; Qin, Jingyu; Li, Hui; Lin, Xiaohang (Frontiers in Chemistry, 2020)
In the present work, a new model of the atomic cluster structure, which is determined by metal Wulff construction with the crystal structure inside, is proposed to describe the structures of metallic melts. The shapes of the structures are determined by surface energies of different crystal plane groups, calculated from density functional theory (DFT), while the size is given by the pair distribution function (PDF) of the experimental high-temperature X-ray diffraction (HTXRD). Taking Aluminum (Al) and Copper (Cu) as the representative examples, we demonstrate that the simulated XRD curves from present models match the experimental results quite well, not only regarding the position and width of the peaks but also the relative intensity of the first and second peaks. These results indicate a successful model to describe the properties of metallic melts. The model also explains a main peak deviation phenomenon between the XRD of metallic melt and the solid ones in pure metal Al. Finally, a physical picture of metallic melt is given, which is mainly composed of atomic cluster structures and free atoms around them.